Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”